Differential modulation of haematopoietic and oxidative injury by PARP-1 and ATR kinase inhibition in a murine model of acute irradiation - Baydaa Taher Sih (PLoS ONE, 2026)
Temporal Modulation of Acute Radiation Injury by Post-Exposure PARP-1 versus ATR Kinase Inhibition. Background PARP-1 and ATR inhibitors have been employed as radiosensitizers in cancer therapy. In addition to this, there is little evidence about the role of these chemicals after a dose of radiation, specifically in relation to reducing damage to healthy cells rather than increasing it. Objective The goal of this study was to determine if PARP-1 or ATR kinase inhibitors, when delayed administered, could decrease the severity of the condition caused by an acute dose of radiation and compare the impact of PARP-1 and ATR inhibitors. Methods Mice of the C57BL/6 strain were subjected to a total body irradiation dose of 2.5 Gy γ-rays. In each experiment, thirty minutes following exposure to IR, either the PARP inhibitor, olaparib at 50 mg/kg or the ATR kinase inhibitor VE-821 at 25 mg/kg was injected intraperitoneally into the mice. The parameters of blood were measured at the same time as oxidative stress, including the activity of superoxide dismutase and levels of malondialdehyde. Examination of DNA damage and repair dynamics was done through the use of γ-H2AX immunofluorescence. Results Following exposure to ionising radiation, mice which had received a PARP inhibitor showed less marked haemoglobin reduction and less radiation-induced leucopenia than control mice exposed to radiation alone. The modifications were accompanied by a decrease in lipid peroxidation plus enhanced antioxidant activity. This observation that PARP inhibition enhances repair of DNA double-strand breaks is consistent with earlier data from other researchers. In contrast the protective effects of the ATR kinase inhibitor were not apparent when administered after the DNA damage had been inflicted in any of the parameters examined. Conclusion While administering PARP inhibitors following the exposure to ionising radiation was found to reduce the severity of the condition experienced by the subject, as a result of acute radiation syndrome, the same was not seen when the treatment with ATR inhibitors was given to affected subjects. The results of this study show the significance of administering therapeutic agents at the right time to stop the injury to normal cells when DNA repair pathways are activated by exposure to ionising radiation.